Analysis of Alloy Piping Operations in the Muara Tawar PLTGU Project - Yoel, Rendy; Abduh, Muhammad; Fatima, Ima (Jurnal Locus Penelitian dan Pengabdian, 2025)
Productivity in construction work is one of the important factors to be able to manage the expenses of a project. One way to find out work productivity is by conducting simulations. This study specifically conducted a study related to the productivity of alloy piping work in the Muara Tawar PLTGU project. Considering that this work requires a lot of resources, and is on a critical track of project completion schedule. Based on CYCLONE modeling and the results of EZSTROBE software simulation, a productivity of 10.66 diainch/day per team was obtained. However, these results can still be optimized up to 15.99 Dia inch/day per team by adding resources to the fitup job.